The area of residence, legal status and directions of economic activity of the Wallachians / Vlachs in the Middle Ages and the early modern era - Czamańska, Ilona (Balcanica Posnaniensia. Acta et studia, 2021)
This article is devoted to the scope of Vlach settlement, Vlach law and its functioning, as well as the socio-economic role of the Vlachs in Central European and Balkan areas. The source material at our disposal does not allow us to define any clear direction for the expansion of the Vlachs as an ethnos, especially since it evolved very quickly in some areas, but undoubtedly, when the Vlachs appear in the sources, their presence is possible to be traced from the Chalkidiki Peninsula to the Carpathians. By observing the functioning of the Vlach law, we can observe a similar development in the entire territory where it was applied, including the countries of Western European and Byzantine-Orthodox tradition, or the Ottoman Empire. Also the evolution of this law was similar and occurred at a similar time. We can observe the following stages of this evolution: 1. till 14th century: shaping the social and self-government system of Vlach communities 2. 14th –16th centuries: settlement processes and intensive colonization under the Vlach law 3. 16th –18th centuries: taking up agricultural activities by some Vlachs and their loss of the Vlach law 4. 15th –18th centuries: using the principles of Vlach law to build the legal status of Military Borderlands 5. 14th –18th centuries: accession of knez, voivodes and primićurs to the nobility or the timariot class Vlachs, despite their seemingly primitive way of life and management, played an important civilizational role, enabling the economic use of hard-to-reach and dangerous areas.